Complementary feeding methods and introduction of ultra-processed foods: A randomized clinical trial - Moreira, Paula Ruffoni; Nunes, Leandro Meirelles; Giugliani, Elsa Regina Justo; Gomes, Erissandra; Führ, Jordana; Neves, Renata Oliveira; Belin, Christy Hannah Sanini; Bernardi, Juliana Rombaldi (Frontiers in Nutrition, 2022)
Introduction Complementary feeding (CF) is defined as a period when foods, other than milk, are introduced to the infant’s diet. Unfortunately, frequent consumption of ultra-processed foods (UPF) has become highly prevalent early in an infant’s life. The aim was to verify the association of CF methods with the introduction of UPF in early childhood. Methods This randomized clinical trial involved pairs of mother-infants, allocated in groups receiving different CF interventions: strict Parent-Led Weaning (PLW); strict Baby-Led Introduction to SolidS (BLISS), or mixed-method. The intervention consisted of a counseling session on healthy eating at the child’s 5.5 months of age. A structured questionnaire was created based on the NOVA classification for the definition of UPF and applied at 9 and 12 months. The effect of the CF method intervention was measured by a survival curve for UPF offered for the first time in early childhood between groups. Cox regression was used to estimate its magnitude. The primary analysis was done in three groups (PLW, BLISS, and Mixed) and the secondary analysis was done in two groups (PLW, and BLISS + Mixed). Results A total of 139 mother-infant pairs were eligible and 129 followed the study. The prevalence of infants who were exposed to UPF in early childhood was 58.9% (n = 76), being 71.4% in the PLW group, 53.3% in the BLISS group, and 52.4% in the Mixed group, without differences between them (p = 0.133). The PLW group intervention had a greater chance of exposure to ice cream or popsicles (p = 0.032) and sweet crackers (p = 0.009), compared with the other two CF groups. The Cox regression did not find significant differences between the three groups. However, the regression with two groups estimated a 38% reduction in the offer of UPF in the BLISS + Mixed group intervention (p = 0.049). Discussion The CF intervention promoting greater infant autonomy (BLISS and Mixed) was associated with a reduction in the offer of UPF in early childhood. This knowledge may contribute to supporting strategies aimed at reducing UPF consumption by the young infant. Brazilian registry of clinical trials (ReBEC) [https://ensaiosclinicos.gov.br/rg/RBR-229scm], identifier [RBR-229scm U1111-1226-9516].